Матеріально-побутова сфера жителів міста Луцька в умовах зниження рівня життя в Україні - Павлючик, Валентина Валеріївна; Павлючик, Валентина Валерьевна; Pavliuchyk, Valentyna V. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Економічна криза, політична нестабільність та військовий конфлікт в Україні актуалізують вивчення рівня життя населення, зниження якого зафіксували дані статистики у 2013 р., а соціологічних опитувань – у 2014 р. За даними моніторингів соціального самопочуття, проведених у Луцьку (2009, 2014, 2015), ще у 2014 р. лучани «задумувалися» про речі другої необхідності (зріс попит на автомобіль, поширилася потреба в модному одязі), уже наступного року їм знову, як у 2009 р., не вистачає речей першої необхідності (продуктів, одягу), зі зростанням цін на продукти та житлово-комунальні послуги зріс попит на присадибну ділянку, знизився – на автомобіль. Проте індекси достатності благ матеріально-побутової сфери 1-го та 2-го рівнів лишаються вищими за середній (2,51 і 2,15, відповідно), і наявним рівнем життя в умовах соціальної небезпеки та кризи жителі міста готові вдовольнитися. The economic crisis combined with political instability and military conflict in Ukraine actualizes the study of living standards, particularly through material and domestic sphere of inhabitants of a town as a representative of reaction to social changes. Statistical data recorded the decrease of living standards in the country in 2013, however, the results of sociological surveys showed that only in 2014 it became noticeable for Ukrainians. According to sociological research conducted in Lutsk (2009, 2014, 2015), in 2014 Lutsk inhabitants “were still thinking” about secondary needs (the car demand, and the need for fashionable clothes has increased). However, already in 2015, like in 2009, townspeople were lacking basic needs (food, clothes); with the food prices and communal services one increase, the demand for farmland as an alternative for growing food and building a house increased, whereas demand for the car decreased. However, Sufficiency Indexes of material and domestic sphere of the 1st and the 2nd levels remain higher than average (2,51 and 2,15 accordingly in 2015), and the available living and the material level under conditions of social danger and crisis is sufficient for town inhabitants.
The Material and Domestic Sphere of Lutsk Inhabitants under Conditions of Decrease the Living Standards in Ukraine
Keywords: матеріальне становище; рівень життя; бідність; соціальні блага; жителі Луцька; material status; living standards; poverty; social benefits; inhabitants of Lutsk